LEADERSHIP INNOVATION PRACTICES AND QUALITY EDUCATION IN CAPIZ - Glemer, Ma Fe; Vasquez, Michael B (President University, 2024)
Leadership is ever-evolving with approaches that employ innovation addressing institutional context-specific challenges while manifesting a level of quality. Employing a mixed-method research approach using explanatory sequential design, this study delves on leadership in the academe to uplift quality education through innovation practices for the development of learners to be globally capable in the future. Hence, this study described, differentiated, and correlated leadership innovation practices and quality education in Capiz as perceived by the 255 randomly selected integrated school teachers and 8 FGD participants coming from the Schools Divisions of Roxas City and Capiz respectively. Frequency, percentage, mean, t-test, ANOVA, and Pearson r were used to analyze the data from researcher-made questionnaires while the qualitative data were thematically analyzed. Results showed that leadership innovation practices as manifested by the school heads were significantly manifested through concrete pieces of evidence in addressing, valuing, and designing strategic innovative practices in terms of service, process, and marketing; quality education was comprehended as significantly manifested through policies and considering issues in the educative process reflective of quality in terms of accessibility, pedagogical leadership, and evidence-based practices; leadership innovation practices had a significant difference only when educational attainment of the respondents was considered; the demographics of the respondents did not affect the quality education; and, leadership innovation practices and quality are mutually dependent. Thus, leadership innovation schemes vis-à-vis school-based management strategies may be considered to enhance innovative facets of school management. Future investigation in leadership, innovation, and quality education is further recommended.